2008
DOI: 10.1111/j.1541-0420.2007.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Predictive Performance of Prognostic Models for Censored Survival Data with Time‐Dependent Covariates

Abstract: Prognostic models in survival analysis typically aim to describe the association between patient covariates and future outcomes. More recently, efforts have been made to include covariate information that is updated over time. However, there exists as yet no standard approach to assess the predictive accuracy of such updated predictions. In this article, proposals from the literature are discussed and a conditional loss function approach is suggested, illustrated by a publicly available data set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 38 publications
1
66
0
Order By: Relevance
“…We have exemplified and illustrated the some of the most popular and currently available approaches by means of the data of the epo study (Henke et al, 2006) where we have studied epo treatment success and local disease free survival as two different status response variables. For the latter it would also be possible to include time-dependent information in the risk prediction model; for a recent concept of quantifying the prediction performance in such a situation we refer to Schoop et al (2008). We have shown that various performance measures will fit into this general framework the most prominent ones being the Brier score and ROC-based quantities.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…We have exemplified and illustrated the some of the most popular and currently available approaches by means of the data of the epo study (Henke et al, 2006) where we have studied epo treatment success and local disease free survival as two different status response variables. For the latter it would also be possible to include time-dependent information in the risk prediction model; for a recent concept of quantifying the prediction performance in such a situation we refer to Schoop et al (2008). We have shown that various performance measures will fit into this general framework the most prominent ones being the Brier score and ROC-based quantities.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…A corresponding adaptation of our estimator is suggested in Schoop (2008, chapter 5) using the methodology presented in Schoop et al (2008). Acknowledgment…”
Section: Discussionmentioning
confidence: 99%
“…A more general approach like this one is called "dynamic prediction" with CS constituting its simplest form. Dynamic predictions can be derived from multistate models and/or joint models for longitudinal and time-to-event data (4); statistical methods for development and assessment are available (16), but are beyond this contribution.…”
Section: Discussionmentioning
confidence: 99%